If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5h = 7 + 2h Solving 3 + 5h = 7 + 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. 3 + 5h + -2h = 7 + 2h + -2h Combine like terms: 5h + -2h = 3h 3 + 3h = 7 + 2h + -2h Combine like terms: 2h + -2h = 0 3 + 3h = 7 + 0 3 + 3h = 7 Add '-3' to each side of the equation. 3 + -3 + 3h = 7 + -3 Combine like terms: 3 + -3 = 0 0 + 3h = 7 + -3 3h = 7 + -3 Combine like terms: 7 + -3 = 4 3h = 4 Divide each side by '3'. h = 1.333333333 Simplifying h = 1.333333333
| 8(4r-9)=r+27 | | x+(x+4)+(x+8)=21 | | -7-(n-1)=-6(1-2n) | | y=x^2+7x+9 | | 4x-11=x-9 | | 3a+3=54 | | 8(-1+5x)=112 | | 30=9x+y | | x+10-7=4(x+6)-2(3x+3) | | 103-x=2x+6x-7 | | 8w-13w=25 | | 7b^2+-14b+1=0 | | 4x+11=5x-5 | | 4x+8=2x+31+51 | | 12+40=62 | | 3k-1=7x+2 | | 6+2(x+7)=10-3(x-3) | | 40x^2-x+4000=0 | | 5x+11=5x-5 | | 16+8y=48 | | -1+2-(-3)=10 | | -4j=39 | | -34-5x=-12x+64 | | A+2=12 | | 4x+8+2x+3=51 | | -4(x-1)+2x=34+3x | | 7b^2+-14b+7=0 | | -3x-86=-9x+82 | | -7k-2k= | | -6-z=12 | | (4x^2+2)-(2x^2+3)= | | 11x-61=6x+89 |